The Effect of Service Quality And Product Quality on Purchase Decisions at UD Zelindriya Jaya - Syafrizal Syafrizal; July Setiawan (EAJ (Economic and Accounting Journal), 2021)
The furniture industry is one of the growing industrial sectors in Indonesia. There have been problems during the Covid-19 pandemic that have caused chaos in the furniture industry sector. The real impact caused by Covid-19 is a decrease in buying and selling activities, raw materials are difficult to obtain, distribution is hampered, service providers are infected to Covid-19. This study aims to analyze the effect of Service Quality and Product Quality on Purchase Decisions. The population in this study were UD Zelindriya Jaya customers as many as 80 customers. Data analysis using Classical Assumptions.